Ez-Arabic untuk kanak-kanak = EZ-Arabic for chidren - Sahrir, Muhammad Sabri; Yahaya, Mohd Firdaus; Nasir, Mohd Shahrizal (Ministry of Education, Malaysia, 2013)
This innovation features a virtual Arabic learning tool prototype which is specifically designed for learners at primary schools in Malaysia. The prototype provides a new learning experience for students who have been through the traditional Arabic teaching and learning methods by immersing into the attractive, interesting and interactive virtual learning environment. The prototype is still in its design and development stage by analysing the feedbacks from selected teachers and pupils from Malaysian primary schools. The prospect potential market and use of this product are wide; it includes schools, universities and other learning institutions, special programmes e.g. J-Qaf, KAFA and states religious schools.